2017
DOI: 10.15376/biores.12.1.1960-1967
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Phenol Formaldehyde Hybrid Composites Reinforced with Natural Cellulose Fibers

Abstract: This paper reports on the preparation and mechanical properties of hybrid polymer composites involving areca fine fibers (AFFs), sisal fibers (SFs), and roselle fibers (RFs) as reinforcing agents in a phenol formaldehyde (PF) resin-based polymer matrix. For comparative study, an AFF/glass fiber-reinforced PF hybrid composite and AFF/PF composite were also prepared. Hybrid composites were fabricated using a hand lay-up technique, where the weight fraction of fibers was kept at 40 wt% at a ratio of 1:1. Tensile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Sreekala et al [4] studied the influence of fiber surface modifications on the mechanical performance of oil palm fiber-reinforced phenol formaldehyde composites and found that composites having the modified fibers show the excellent impact resistance. Many numbers of researchers have been carried out the performance study on the natural cellulose fiber-reinforced phenol formaldehyde composites: grass/phenol formaldehyde [5], Wereca /roselle/phenol formaldehyde [6], sisal/phenol formaldehyde [7], Wereca/phenol formaldehyde [8], banana/phenol formaldehyde [9], Grewia optiva/phenol formaldehyde [10], and Calotropis Gigantea/phenol formaldehyde [11]. All the above research works report that the phenol formaldehyde composites can be prepared using the natural cellulose fibers as reinforcing agents with the improved properties.…”
Section: Introduction mentioning
confidence: 99%
“…Sreekala et al [4] studied the influence of fiber surface modifications on the mechanical performance of oil palm fiber-reinforced phenol formaldehyde composites and found that composites having the modified fibers show the excellent impact resistance. Many numbers of researchers have been carried out the performance study on the natural cellulose fiber-reinforced phenol formaldehyde composites: grass/phenol formaldehyde [5], Wereca /roselle/phenol formaldehyde [6], sisal/phenol formaldehyde [7], Wereca/phenol formaldehyde [8], banana/phenol formaldehyde [9], Grewia optiva/phenol formaldehyde [10], and Calotropis Gigantea/phenol formaldehyde [11]. All the above research works report that the phenol formaldehyde composites can be prepared using the natural cellulose fibers as reinforcing agents with the improved properties.…”
Section: Introduction mentioning
confidence: 99%
“…As propriedades dos termorrígidos como elevada resistência a estresse, temperatura, dentre outras, devido sua estrutura altamente entrecruzada após a cura (ATHIJAYAMANI et al, 2017) os tornam atrativos. Porém, o entrecruzamento leva a baixa resistência a fraturas, tornando-os mais frágeis do que os termoplásticos, necessitando assim da utilização de um material como reforço estrutural que leva à formação de compósitos.…”
Section: Fonte: Saunders (1998)unclassified